2020
DOI: 10.1097/acm.0000000000003085
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Evidence-Based Medicine to Medical Students Using Wikipedia as a Platform

Abstract: Problem While ideal curricular structures for effective teaching of evidence-based medicine (EBM) have not been definitively determined, optimal strategies ensure that EBM teaching is interactive and clinically based, aligns with major trends in education and health care, and uses longitudinally integrated, whole-task activities. Approach The authors developed a longitudinal, semester-long project, embedded in a first-year medicine course, through which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…Courses were offered solely to medical students and pharmacy students, while one was interdisciplinary. Three authors reported multiple offerings of the course making it difficult to discern the number of enrolled students per offering [11,13,14].…”
Section: Literature Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Courses were offered solely to medical students and pharmacy students, while one was interdisciplinary. Three authors reported multiple offerings of the course making it difficult to discern the number of enrolled students per offering [11,13,14].…”
Section: Literature Resultsmentioning
confidence: 99%
“…Four instructors analyzed the number of student edits made and references added or deleted to students' to assess the quality and potential impact on Wikipedia [11][12][13][14]. Instructors also tracked the durability of student edits such that they were not reversed and used this as an indicator of quality edits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While early introducing undergraduate medical students to the basics of EBM is important to improve their critical thinking [2], and raise their awareness about how medical knowledge is actually built over years of translational research, it might seem difficult to make them understand and accept its common frustrating pitfalls, and to explain how these limitations are part of the whole process effectiveness. Interestingly, this current ongoing COVID-19 pandemic represents a comprehensive and easily perceptible teaching example.…”
Section: Letter To the Editormentioning
confidence: 99%
“…For example, at the University of California, San Francisco, faculty offer medical and pharmacy students courses on improving Wikipedia's quality [11,12]. At Queen's University, all first-year medical students are required to take the course, Critical Appraisal, Research and Lifelong Learning, a major component of which trains students to critically assess and contribute to Wikipedia's medical content [13]. The efforts of the Queen's University students in 2017 amounted to more than 1700 edits on 17 health topics, which were viewed over 3 million times in under a year.…”
Section: Introductionmentioning
confidence: 99%